Layer-specific global longitudinal strain as predictor for arrhythmic subrogates in arrhythmic risk of arrhythmogenic cardiomyopathy: beyond ejection fraction. (4th February 2022) - Segura Rodriguez, D; Bermudez-Jimenez, FJ; Gonzalez Camacho, L; Moreno Escobar, E; Bautista-Paves, A; Oyonarte-Ramirez, JM; Tercedor Sanchez, L; Jimenez-Jaimez, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Arrhythmogenic Cardiomyopathy (AC) is a life-threatening disease which predispose to malignant arrhythmias and sudden cardiac death (SCD) even in early stages of the disease. Risk stratification relies on electrical, genetic and imaging data. Our aim is to investigate how myocardial deformation parameters may identify subjects at risk of ventricular arrhythmias. Methods: A cohort of 45 subjects with definite or borderline diagnosis of AC was characterized using advanced transthoracic echocardiography (TTE) and cardiac magnetic resonance and divided into groups according  surrogates such as non-sustained ventricular tachycardia (NSVT), late gadolinium enhancement (LGE) and genetic status. Layer-specific global longitudinal strain (GLS) by TTE 2D Speckle Tracking was compared in patients with and without these arrhythmic risk markers. Results: Twenty-three (51.1%) patients were men, mean age 43 ± 16 years. Next-generation sequencing identified a potential pathogenic mutation in 39 (86.7%) patients. Thirty-nine patients presented LGE (73.3%), mostly located at the subepicardial-to-mesocardial layers. Layer-Specific-GLS analysis showed worse GLS values at the epicardial and mesocardial layers in subjects with NSVT and LGE. Epicardial GLS values of -15.4% and -16.1% were the best cut-off values for identifying individuals with NSVT and LGE, respectively (figure 1, panel A and B, respectively) regardless of left ventricular ejection fraction. Conclusions: Layer-specific GLS assessment identified subjects with high-risk arrhythmic features in AC such as NSVT and LGE. Epicardial GLS may emerge as potential instrument for detecting subjects at risk of SCD in AC.